Energy Consumption Forecasting Using Semantic-Based Genetic Programming with Local Search Optimizer - Castelli, Mauro (2015)
Castelli, M., Trujillo, L., & Vanneschi, L. (2015). Energy Consumption Forecasting Using Semantic-Based Genetic Programming with Local Search Optimizer. Computational Intelligence And Neuroscience, 2015, [971908]. https://doi.org/10.1155/2015/971908